The first purge [videorecording (DVD)] - Noel, Y'lan; Davis, Lex Scott, 1991-; Wade, Joivan, 1993- (Univeral Pictures Home Entertainment, 2018)
Behind every tradition lies a revolution. Next Independence Day, witness the rise of our country's twelve hours of annual lawlessness. Welcome to the movement that began as a simple experiment. To push the crime rate below one percent for the rest of the year, the New Founding Fathers of America (NFFA) test a sociological theory that vents aggression for one night in one isolated community. But when the violence of oppressors meets the rage of the marginalized, the contagion will explode from the trial-city borders and spread across the nation.